2016
DOI: 10.4269/ajtmh.16-0215
|View full text |Cite
|
Sign up to set email alerts
|

Reannotation of Yersinia pestis Strain 91001 Based on Omics Data

Abstract: Abstract. Yersinia pestis is among the most dangerous human pathogens, and systematic research of this pathogen is important in bacterial pathogenomics research. To fully interpret the biological functions, physiological characteristics, and pathogenesis of Y. pestis, a comprehensive annotation of its entire genome is necessary. The emergence of omicsbased research has brought new opportunities to better annotate the genome of this pathogen. Here, the complete genome of Y. pestis strain 91001 was reannotated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
2
0
1
Order By: Relevance
“…Genome của tằm đã được giải trình tự và lắp ráp khá chắc chắn, nhưng chú giải chính xác về bộ gen đối với các vấn đề sinh học hiện đại vẫn chưa hoàn chỉnh. Để cải thiện phần chú giải nay, nhóm Ye X và đồng tác giả đã thực hiện phân tích proteogenomics, sử dụng 9,8 triệu phổ khối thu thập từ các mô khác nhau ở các giai đoạn phát triển của tằm (Ye et al, 2019 Dựa trên các dữ liệu về proteogenomics, Mao và đồng tác giả chú giải lại bộ gen của chủng Yersinia pestis 91001, loại bỏ 137 CDS không đáng tin cậy, tái định vị TIS cho 41 gen tương đồng và sửa đổi chức năng của 7 pseudogenes và 392 gen giả định (Mao et al, 2016). Một nghiên cứu proteogenomics của Rang và đồng tác giả cho thấy 39 trình tự mã hóa trong toàn bộ bộ gen của Bacillus thuringiensis có liên quan đến khả năng gây bệnh của côn trùng, bao gồm 5 gen cry.…”
Section: Proteogenomics Và Các Vấn đề Trong Chú Giải/chú Giải Lại Gen/hệ Genunclassified
“…Genome của tằm đã được giải trình tự và lắp ráp khá chắc chắn, nhưng chú giải chính xác về bộ gen đối với các vấn đề sinh học hiện đại vẫn chưa hoàn chỉnh. Để cải thiện phần chú giải nay, nhóm Ye X và đồng tác giả đã thực hiện phân tích proteogenomics, sử dụng 9,8 triệu phổ khối thu thập từ các mô khác nhau ở các giai đoạn phát triển của tằm (Ye et al, 2019 Dựa trên các dữ liệu về proteogenomics, Mao và đồng tác giả chú giải lại bộ gen của chủng Yersinia pestis 91001, loại bỏ 137 CDS không đáng tin cậy, tái định vị TIS cho 41 gen tương đồng và sửa đổi chức năng của 7 pseudogenes và 392 gen giả định (Mao et al, 2016). Một nghiên cứu proteogenomics của Rang và đồng tác giả cho thấy 39 trình tự mã hóa trong toàn bộ bộ gen của Bacillus thuringiensis có liên quan đến khả năng gây bệnh của côn trùng, bao gồm 5 gen cry.…”
Section: Proteogenomics Và Các Vấn đề Trong Chú Giải/chú Giải Lại Gen/hệ Genunclassified
“…Among these, the bestdocumented contribution of proteogenomics lies in the annotation of newly sequenced non-model organisms [3]. Besides, proteogenomics is applied in genome re-annotation whereby it has helped to correct misannotated genes [4], and to detect novel coding sequences (CDS) previously thought to be non-coding; such as pseudogenes, short open reading frames (sORFs) and other non-coding RNA genes [5,6]. Apart from that, it has assisted in unraveling the undiscovered protein counterparts of annotated genes, the so-named "missing proteins" [7].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-genome microarrays in Y. pestis KIM6+ showed that y2570 had significantly higher expression levels in the flea gut but not the rat bubo (Vadyvaloo et al, 2010 ). We predicted and identified that bfvR , located between the bases 1,639,340 and 1,639,726 on the genome of Microtus strain 91001, can participate in biofilm formation in vivo (Song et al, 2004 ; Mao et al, 2016 ). In this research, we also studied the regulation mechanisms on biofilm formation for the mentioned genes by BfvR in Y. pestis .…”
Section: Introductionmentioning
confidence: 99%